2019
DOI: 10.5194/se-2019-50
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can anaerobic oxidation of methane prevent seafloor gas escape in a warming climate?

Abstract: Assessments of future climate warming-induced seafloor methane (CH4) release rarely include anaerobic oxidation of methane (AOM) within the sediments. Considering that more than 90% of the CH4 produced in ocean sediments today is consumed by AOM, this may result in substantial overestimations of future seafloor CH4 release. Here we integrate a fully coupled AOM module with a 15 numerical hydrate model to investigate under what conditions rapid release of CH4 can bypass AOM and result in significant fluxes to t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This result implies that the advective flux of methane is not entirely accessible to sulfate reduction 6,43 . The mechanisms by which a focused methane flow migrates through the sediment to bypass the sulfate reduction filter remain poorly understood, but recent numerical modelling has shown that rapid gas hydrate dissociation in sediments at shallow depths (<14 m) below seafloor may create hydraulic fractures that focus methane flow 44 , producing a flux that cannot be entirely consumed by sulfate reduction 45 . Our results are therefore consistent with a highly focused massive advective flux of methane within the pockmark field that is bypassing the sulfate reduction filter to form gas flares.…”
Section: Resultsmentioning
confidence: 99%
“…This result implies that the advective flux of methane is not entirely accessible to sulfate reduction 6,43 . The mechanisms by which a focused methane flow migrates through the sediment to bypass the sulfate reduction filter remain poorly understood, but recent numerical modelling has shown that rapid gas hydrate dissociation in sediments at shallow depths (<14 m) below seafloor may create hydraulic fractures that focus methane flow 44 , producing a flux that cannot be entirely consumed by sulfate reduction 45 . Our results are therefore consistent with a highly focused massive advective flux of methane within the pockmark field that is bypassing the sulfate reduction filter to form gas flares.…”
Section: Resultsmentioning
confidence: 99%
“…Linke et al (1994) measured a fluid velocity as high as 10 5 cm/yr in seep sites, and calculated a methane flux of 120 mmol/(m 2 day) on Hydrate Ridge. Stranne et al (2019) suggested that fracture flow with high velocities could weaken the SD-AOM efficiency by numerical simulation. In addition, polygonal faults developed in fine-grained sediments weaken the seal capacity of marine sediments, providing new pathways for upward water migration (Ma et al, 2021).…”
Section: Contribution Of Water Movementmentioning
confidence: 99%
“…Finally, observations from the ESAS also indicate that methane gas accumulates in the sediments. When free gas pockets grow enough, methane tends to migrate upwards along pathways with higher permeability or where fractures occur (Yakushev, 1989;Boudreau et al, 2005;Wright et al, 2008;Shakhova et al, 2014Shakhova et al, , 2015Shakhova et al, , 2017Leifer et al, 2017) and might even crack the sediments themselves (O'Connor et al, 2010;Overduin et al, 2016;Yao et al, 2019;Stranne et al, 2019). However, despite a wealth of AOM-related research, a holistic, quantitative evaluation of the most important environmental controls on the efficiency of the AOM biofilter and its impact on methane escape from marine sediments is currently lacking.…”
Section: Introductionmentioning
confidence: 99%